INDIKASI DAN TEKNIK PEMASANGAN ALAT PACU JANTUNG PERMANEN - Dwiana Cahyaningrum (UHAMKA Press, 2020)
Permanent pacemaker is effective therapy to handle heart rythm abnormalities (arrhytmia) such as AV Block,Sinus Node Dysfunction, and Fascicular Block. Permanent pacemaker has basic principles which is stimulatingand pacing impuls from pulsation generator and delivered by lead to myocardium so the heart can depolarizedproperly. Implantation technique and choosing pacing mode on each device are different according to theindications that occur. As the development of technology creates medical innovation is a leadless pacemaker withadvantages reduce complications that occur when device implantation compare to permanent pacemaker(conventional pacemaker).